LEGENDE POPULARE GEOGRAFICE (PANGEEA, 2025)
Ge geographical popular legends. Put together, the legendary fancies on the origin and toponymy of mountains, hills and waters personify a real Romanian spiritual geography. In conceiving the legends referring to the genesis of the natural forms, the popular creators start from observing the distinctive features of some rocks, valleys and rivers; then they associate these specific data with comparative terms, making up a story around each of these analogies. Keywords: legend;toponymy;natural forms;folklore;genesis Strânse laolaltă, plăsmuirile legendare despre originea şi toponimia munţilor, dealurilor, apelor întruchipează o adevărată geografie spirituală românească.